Flexible flame-retardant aerogel and preparation method thereof
By using the DA reaction of modified graphene with the OLED screen backsheet and the modified polyvinyl alcohol crosslinking network, the adhesion problem between the aerogel layer and the screen backsheet was solved, achieving non-destructive rework and excellent overall performance.
Patent Information
- Application Number
- CN202511468595.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-11-14
AI Technical Summary
In existing technologies, adhesives are commonly used to bond the aerogel layer to the back panel of the OLED screen, which leads to a decrease in flexibility. This is especially true for foldable phones, where the adhesive is prone to peeling and delamination, and it is difficult to rework without damage.
By conducting a DA reaction between modified graphene and maleimide groups modified on the surface of the OLED screen backsheet, a reversible covalent bond is formed, avoiding the use of adhesives. Furthermore, the heat resistance and flexibility of the material are improved by utilizing the crosslinking network of modified polyvinyl alcohol and epoxy resin.
It achieves non-destructive bonding between aerogel and OLED screen backsheet, maintaining the material's flexibility and heat resistance, while providing excellent flame retardant, electromagnetic shielding and thermal insulation properties, and the reversible reaction facilitates non-destructive rework.
Smart Images

Figure CN120944269A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel technology, specifically a flexible flame-retardant gel and its preparation method. Background Technology
[0002] Aerogel, as an emerging flexible electronic material, forms a continuous conductive network by embedding conductive nanomaterials within it. This network can reflect and absorb electromagnetic waves, and its extremely low thermal conductivity allows for the integration of an ultrathin, flexible, flame-retardant aerogel layer between the OLED screen and the motherboard of a mobile phone. This effectively provides the screen with both a "heat shield" and an "electromagnetic shield," reducing heat conduction and maintaining the screen's operating temperature at a low and stable level, thus significantly delaying aging. It also prevents electromagnetic interference with the screen's display and touch signals. However, the adhesives used to bond the aerogel layer to the screen back panel may affect the aerogel's flexibility, especially for foldable phones. Under repeated bending, the adhesive layer may delaminate or peel due to interfacial stress concentration. Summary of the Invention
[0003] (1) Technical problems to be solved The purpose of this invention is to provide a flexible flame-retardant aerogel and its preparation method, which enables the aerogel to be directly bonded to the back of an OLED screen through chemical bonding, avoiding the use of adhesives.
[0004] (2) Technical solution To achieve the above objectives, on the one hand, the present invention provides a flexible flame-retardant gel comprising the following raw materials in parts by weight: 5-10 parts modified graphene, 50-80 parts modified polyvinyl alcohol, 3-5 parts silver nanowires, 7-10 parts phytic acid, and 5-7 parts epoxy resin E-51. Modified graphene was hydrophobically treated and grafted with furan groups; Modified polyvinyl alcohol grafted with sterically hindered amine groups and PEG long chains.
[0005] Furthermore, the preparation method of the modified graphene includes the following steps: S11. Mix concentrated H2SO4 and H3PO4 in an ice bath and stir continuously. Add graphite powder and disperse evenly. Slowly add KMnO4 in batches. Remove the ice bath, heat and stir the reaction. Cool the resulting reaction solution in an ice bath, add deionized water, add H2O2 solution dropwise, centrifuge to collect the solid, wash with dilute hydrochloric acid and deionized water, dialysis to purify, and freeze-dry to obtain graphene oxide. S12. Disperse graphene oxide in deionized water, ultrasonically disperse, and adjust the pH to weakly alkaline to obtain a graphene oxide dispersion. S13. Add silane coupling agent KH570 to the graphene oxide dispersion, stir and react, centrifuge the resulting reaction solution to collect the solid, wash with deionized water, freeze dry to obtain hydrophobic graphene oxide; S14. Disperse hydrophobic graphene in DMF, add furanol methanol and p-toluenesulfonic acid, reflux the reaction, centrifuge the resulting reaction solution to collect the solid, wash with ethanol and deionized water, and vacuum dry to obtain modified graphene.
[0006] Furthermore, the mass ratio of graphene oxide, furanol, and KH570 is 1:8~9:7~8, and the mass of p-toluenesulfonic acid is 3% of the mass of furanol.
[0007] Furthermore, the preparation method of the modified polyvinyl alcohol includes the following steps: S21. Dissolve polyvinyl alcohol in anhydrous DMSO, cool the resulting solution, add DBTL, and then slowly add a DMSO solution of DBU-(CH2)3-NCO. Stir the reaction to obtain the first compound. S22. Cool the first compound, pour it into ice-cold acetone to precipitate, collect the solid by centrifugation, wash it repeatedly with acetone and centrifuge, and dry it under vacuum to obtain the second compound. S23. Dissolve mPEG and HDI in anhydrous DMF, add DBTL, activate the reaction, and obtain the third compound; S24. The second compound was heated and dissolved in anhydrous DMF, the third compound was slowly added dropwise, followed by DBTL, and the reaction was heated. The resulting reaction solution was cooled and poured into ice-cold ether to precipitate. The solid was collected by centrifugation, washed repeatedly with ether by centrifugation, and dried under vacuum to obtain modified polyvinyl alcohol.
[0008] Furthermore, the mass ratio of polyvinyl alcohol, DBU-(CH2)3-NCO, and mPEG is 5:1.5~2:24~27, and the molar ratio of mPEG to HDI is 3:1.
[0009] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a flexible flame-retardant gel, applicable to the aforementioned flexible flame-retardant gel, comprising the following steps: S1. Dissolve modified polyvinyl alcohol in DMSO with stirring to obtain solution A; disperse modified graphene in deionized water with ultrasonication to obtain suspension B; disperse silver nanowires in anhydrous ethanol with ultrasonication to obtain suspension C; dissolve epoxy resin E-51 and phytic acid in DMSO to obtain solution D. S2. While stirring, slowly pour solution A into suspension B, sonicate to disperse evenly, slowly add suspension C and stir evenly, continue to add solution D, continue to stir and mix evenly to obtain the first mixture; S3. Add pentanediol aqueous solution to the first mixture, add HCl dropwise to adjust the pH, let the reaction stand, and obtain the second mixture; S4. Dissolve methyltetrahydrophthalic anhydride and zinc acetylacetonate in DMSO to obtain solution E, slowly diffuse it into the second mixture, heat and solidify to obtain the third mixture; S5. Immerse the third mixture in ethanol, allow it to age by displacement, remove the solid, and dry it with supercritical CO2 to obtain an aerogel.
[0010] Furthermore, the concentration of ethanol in S5 is 25%, 50%, 75%, or 100%, and each soaking lasts for 8 hours.
[0011] The specific application scenarios of this invention are described below: High temperatures are one of the main causes of aging and color shift in OLED screens. To isolate the screen from the heat generated by the motherboard chip and protect it from internal electromagnetic interference, an aerogel layer is bonded between the OLED display film and the motherboard. Currently, adhesives are generally used to bond the aerogel to the OLED display. However, on the one hand, modern mobile phones, especially foldable phones, are increasingly pursuing ultra-thin designs, and using adhesives would affect the phone's thickness. On the other hand, the physical adsorption between adhesives and materials is weak, and rework is difficult. Therefore, this invention is based on the thermally reversible chemistry of the DA reaction, which allows the furan groups on the aerogel surface to come into contact with the maleimide groups modified on the OLED screen back panel under pressure at 80°C, resulting in a DA reaction and forming a strong covalent bond interface. Because this reaction is reversible, when repair is needed, the screen can be locally heated to 120°C, causing the DA bonds to break, the interface to debond, and the aerogel to be removed completely and without damage, achieving non-destructive rework.
[0012] Polyvinyl alcohol (PVA) serves as the matrix for the aerogel, providing film-forming properties and flexibility. The flexible network of PVA, combined with the rigid crosslinking of epoxy resin E-51, enhances the material's heat resistance and mechanical strength, preventing creep or deformation during long-term use. Furthermore, PVA is modified by grafting sterically hindered amine groups and long PEG chains. The lone pair electrons of DBU-(CH2)3-NCO interact weakly with the furan groups on the modified graphene, forming a "dynamic protective layer." This prevents side reactions between the furan groups and the epoxy groups of epoxy resin E-51. During subsequent bonding and heating of the aerogel to the OLED screen backsheet, this protective layer reversibly unwinds, exposing reaction sites and facilitating the DA reaction. Modified PVA grafted with mPEG prevents the modified graphene from agglomerating through steric hindrance, ensuring uniform dispersion to construct a highly efficient functional network. The flexibility of mPEG also helps maintain the overall material's flexibility.
[0013] Modified graphene is hydrophobically treated and grafted with furan groups. The nanolayer structure of the graphene oxide substrate effectively scatters phonons, significantly reducing heat conduction and isolating heat from the motherboard to the OLED screen. Furthermore, graphene oxide promotes the formation of a dense carbon layer during combustion, isolating oxygen. In addition, hydrophobic modification reduces the hydrophilicity of graphene oxide, enhancing its compatibility with the PEG long chains and amine chains on modified polyvinyl alcohol. This prevents the modified graphene from agglomerating and settling in the matrix, thus avoiding stress concentration and impairing the material's mechanical properties. The grafted furan groups undergo a DA reaction with maleimide groups, allowing the aerogel to adhere to the OLED screen backsheet.
[0014] Silver nanowires form a highly conductive network, which is the main force providing electromagnetic shielding, effectively protecting the OLED screen from electromagnetic interference from internal motherboard components. Furthermore, the conductive network of silver nanowires intertwines with modified graphene, which has a certain degree of conductivity, synergistically enhancing the electromagnetic shielding effectiveness.
[0015] Phytic acid, as an environmentally friendly flame retardant, catalyzes the dehydration and carbonization of polymers during combustion, forming an expanded and dense char layer that effectively isolates oxygen and heat.
[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention introduces furan groups into the aerogel by modifying graphene, which undergo a DA reaction with the maleimide groups modified on the surface of the OLED screen back panel to form a strong covalent bond interface, avoiding the use of adhesives. Moreover, the DA reaction is reversible, enabling non-destructive rework.
[0017] 2. The flexible network of polyvinyl alcohol and the rigid crosslinking of epoxy resin E-51 improve the heat resistance and mechanical strength of the material. Furthermore, the grafting of sterically hindered amine groups onto PVA results in weak interactions between the lone pairs of electrons and the furan groups on the modified graphene, preventing side reactions between the furan groups and the epoxy groups of epoxy resin E-51. Moreover, when the aerogel is subsequently bonded to the back panel of the OLED screen and heated, this protective layer can be reversibly unwound, exposing the reaction sites and allowing the DA reaction to proceed smoothly.
[0018] 3. The modified graphene is hydrophobically treated to enhance its compatibility with the long PEG chain and amine chain on the modified polyvinyl alcohol. The modified polyethylene grafted with mPEG prevents the modified graphene from agglomerating through steric hindrance, ensuring its uniform dispersion. Attached Figure Description
[0019] Figure 1 This is a flowchart of the aerogel preparation process in Example 1 of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1: This example discloses a flexible flame-retardant gel, comprising the following raw materials in parts by weight: 5 parts modified graphene, 50 parts modified polyvinyl alcohol, 3 parts silver nanowires, 7 parts phytic acid, and 5 parts epoxy resin E-51. Modified graphene was hydrophobically treated and grafted with furan groups; Modified polyvinyl alcohol grafted with sterically hindered amine groups and PEG long chains.
[0022] The method for preparing the modified graphene includes the following steps: S11. Mix concentrated H2SO4 and H3PO4 in an ice bath at a ratio of 9:1 and stir continuously. Add graphite powder and disperse evenly. Slowly add KMnO4 in batches. Remove the ice bath and heat to 35-50°C. Stir and react for 12 hours. Cool the resulting reaction solution in an ice bath. Add deionized water and add H2O2 solution dropwise until the solution turns bright yellow. Centrifuge to collect the solid. Wash with 5% dilute hydrochloric acid and deionized water. Dialyze to purify. Freeze dry to obtain graphene oxide. S12. Disperse graphene oxide in deionized water, ultrasonically disperse, and adjust the pH to 8-9 to obtain a graphene oxide dispersion. S13. Add silane coupling agent KH570 to the graphene oxide dispersion, stir and react at 70~80°C for 12~24 hours, centrifuge the reaction solution to collect the solid, wash with deionized water, freeze dry to obtain hydrophobic graphene oxide; S14. Disperse hydrophobic graphene in DMF, add furanol and p-toluenesulfonic acid, reflux at 100-120°C for 24-48 hours, centrifuge the resulting reaction solution to collect the solid, wash with ethanol and deionized water, and vacuum dry at 40-60°C to obtain modified graphene.
[0023] The mass ratio of graphene oxide, furanol, and KH570 is 1:8:7, and the mass of p-toluenesulfonic acid is 3% of the mass of furanol.
[0024] The method for preparing the modified polyvinyl alcohol includes the following steps: S21. Dissolve polyvinyl alcohol in anhydrous DMSO at 90°C, cool the resulting solution to 75~80°C, add one drop of DBTL, and then slowly add a DMSO solution of DBU-(CH2)3-NCO. Stir the reaction at 80°C for 6~12 hours to obtain the first compound. S22. The first compound was cooled and poured into ice-cold acetone to precipitate. The solid was collected by centrifugation, washed repeatedly with acetone and centrifuged, and dried under vacuum at 50°C to obtain the second compound. S23. Dissolve mPEG and HDI in anhydrous DMF, add one drop of DBTL, and activate the reaction at 60°C for 3-5 hours to obtain the third compound; S24. The second compound is heated and dissolved in anhydrous DMF, the third compound is slowly added dropwise, and then one drop of DBTL is added dropwise. The mixture is heated to 70-80°C and reacted for 12-24 hours. The resulting reaction solution is cooled, poured into ice-cold ether to precipitate, the solid is collected by centrifugation, washed repeatedly by centrifugation with ether, and dried under vacuum to obtain modified polyvinyl alcohol.
[0025] The mass ratio of polyvinyl alcohol, DBU-(CH2)3-NCO, and mPEG is 5:1.5:24, and the molar ratio of mPEG to HDI is 3:1.
[0026] The preparation method of the flexible flame-retardant gel includes the following steps: S1. Dissolve modified polyvinyl alcohol in DMSO under stirring at 90°C to obtain solution A; disperse modified graphene in deionized water by ultrasonication to obtain suspension B; disperse silver nanowires in anhydrous ethanol by ultrasonication to obtain suspension C; dissolve epoxy resin E-51 and phytic acid in DMSO to obtain solution D; S2. While stirring, slowly pour solution A into suspension B, sonicate to disperse evenly, slowly add suspension C and stir evenly, continue to add solution D, continue to stir and mix evenly to obtain the first mixture; S3. Add a 25% pentanediol aqueous solution to the first mixture, add HCl dropwise to adjust the pH to 2-3, let the reaction stand for 1-4 hours to obtain the second mixture; S4. Dissolve methyltetrahydrophthalic anhydride and zinc acetylacetonate in DMSO to obtain solution E, which is then slowly poured into the second mixture and cured by programmed temperature increase of 80~120°C to obtain the third mixture. S5. Immerse the third mixture in ethanol, allow it to age by displacement, remove the solid, and dry it with supercritical CO2 to obtain an aerogel.
[0027] It should be noted that, as Figure 1The diagram shows the aerogel preparation process of Example 1 of this invention. To ensure better compatibility of the raw materials, each material is first prepared into a corresponding solution or suspension, then mixed one by one, accompanied by vigorous mechanical stirring and ultrasonic treatment, to ensure uniform dispersion of the materials. Pentylene glycol is used as a crosslinking agent to achieve crosslinking and gelation of the polyvinyl alcohol network, forming a wet gel. This invention uses low molecular weight epoxy resin E-51, which has good flowability and is easily mixed with polyvinyl alcohol. Methyltetrahydrophthalic anhydride is used as a curing agent to form a second crosslinking network inside the wet gel, significantly strengthening the material. Finally, the aerogel is obtained through ethanol gradient displacement and supercritical CO2 drying.
[0028] The concentration of ethanol in S5 is 25%, 50%, 75%, and 100%, and each soaking lasts for 8 hours.
[0029] Example 2: This example is based on Example 1, but differs from Example 1 in that it is a flexible flame-retardant gel comprising the following raw materials in parts by weight: 7.5 parts modified graphene, 65 parts modified polyvinyl alcohol, 4 parts silver nanowires, 8.5 parts phytic acid, and 6 parts epoxy resin E-51. The other components and preparation methods are the same as in Example 1.
[0030] Example 3: This example is based on Example 1, but differs from Example 1 in that it is a flexible flame-retardant gel comprising the following raw materials in parts by weight: 10 parts modified graphene, 80 parts modified polyvinyl alcohol, 5 parts silver nanowires, 10 parts phytic acid, and 7 parts epoxy resin E-51. The other components and preparation methods are the same as in Example 1.
[0031] Example 4: This example is based on Example 1, but differs from Example 1 in that the mass ratio of graphene oxide, furanol, and KH570 in this example is 1:9:8.
[0032] The other components and preparation methods are the same as in Example 1.
[0033] Example 5: This example is based on Example 1, but differs from Example 1 in that the mass ratio of polyvinyl alcohol, DBU-(CH2)3-NCO, and mPEG in this example is 5:2:27.
[0034] The other components and preparation methods are the same as in Example 1.
[0035] Comparative Example 1: This comparative example is based on Example 1, but differs from Example 1 in that the modified graphene in this comparative example is not hydrophobicated.
[0036] The method for preparing the modified graphene includes the following steps: S11. Mix concentrated H2SO4 and H3PO4 in an ice bath at a ratio of 9:1 and stir continuously. Add graphite powder and disperse evenly. Slowly add KMnO4 in batches. Remove the ice bath and heat to 35-50°C. Stir and react for 12 hours. Cool the resulting reaction solution in an ice bath. Add deionized water and add H2O2 solution dropwise until the solution turns bright yellow. Centrifuge to collect the solid. Wash with 5% dilute hydrochloric acid and deionized water. Dialyze to purify. Freeze dry to obtain graphene oxide. S12. Disperse hydrophobic graphene in DMF, add furanol and p-toluenesulfonic acid, reflux at 100-120°C for 24-48 hours, centrifuge the resulting reaction solution to collect the solid, wash with ethanol and deionized water, and vacuum dry at 40-60°C to obtain modified graphene.
[0037] The other components and preparation methods are the same as in Example 1.
[0038] Comparative Example 2: This comparative example is based on Example 1, but differs from Example 1 in that the modified graphene in this comparative example is not grafted with furan groups.
[0039] The method for preparing the modified graphene includes the following steps: S11. Mix concentrated H2SO4 and H3PO4 in an ice bath at a ratio of 9:1 and stir continuously. Add graphite powder and disperse evenly. Slowly add KMnO4 in batches. Remove the ice bath and heat to 35-50°C. Stir and react for 12 hours. Cool the resulting reaction solution in an ice bath. Add deionized water and add H2O2 solution dropwise until the solution turns bright yellow. Centrifuge to collect the solid. Wash with 5% dilute hydrochloric acid and deionized water. Dialyze to purify. Freeze dry to obtain graphene oxide. S12. Disperse graphene oxide in deionized water, ultrasonically disperse, and adjust the pH to 8-9 to obtain a graphene oxide dispersion. S13. Add silane coupling agent KH570 to the graphene oxide dispersion, stir and react at 70~80°C for 12~24 hours, centrifuge the resulting reaction solution to collect the solid, wash with deionized water, freeze dry to obtain modified graphene.
[0040] The other components and preparation methods are the same as in Example 1.
[0041] Comparative Example 3: This comparative example is based on Example 1, but differs from Example 1 in that the modified polyvinyl alcohol in this comparative example is not grafted with DBU-(CH2)3-NCO.
[0042] The method for preparing the modified polyvinyl alcohol includes the following steps: S21. Dissolve mPEG and HDI in anhydrous DMF, add one drop of DBTL, and activate the reaction at 60°C for 3-5 hours to obtain the third compound; S22. Polyvinyl alcohol is heated and dissolved in anhydrous DMF. The third compound is slowly added dropwise, followed by one drop of DBTL. The mixture is heated to 70-80°C and reacted for 12-24 hours. The resulting reaction solution is cooled and poured into ice-cold ether to precipitate. The solid is collected by centrifugation, washed repeatedly by centrifugation with ether, and dried under vacuum to obtain modified polyvinyl alcohol.
[0043] The other components and preparation methods are the same as in Example 1.
[0044] Comparative Example 4: This comparative example is based on Example 1, but differs from Example 1 in that the modified polyvinyl alcohol in this comparative example is not grafted with mPEG.
[0045] The method for preparing the modified polyvinyl alcohol includes the following steps: S21. Dissolve polyvinyl alcohol in anhydrous DMSO at 90°C, cool the resulting solution to 75~80°C, add one drop of DBTL, and then slowly add a DMSO solution of DBU-(CH2)3-NCO. Stir the reaction at 80°C for 6~12 hours to obtain the first compound. S22. The first compound was cooled, poured into ice-cold acetone to precipitate, the solid was collected by centrifugation, washed repeatedly with acetone and centrifuged, and dried under vacuum at 50°C to obtain modified polyvinyl alcohol.
[0046] The other components and preparation methods are the same as in Example 1.
[0047] Comparative Example 5: This comparative example is based on Example 1, but unlike Example 1, no modified graphene is added.
[0048] The other components and preparation methods are the same as in Example 1.
[0049] Comparative Example 6: This comparative example is based on Example 1, but unlike Example 1, this comparative example does not add epoxy resin E-51.
[0050] The other components and preparation methods are the same as in Example 1.
[0051] Comparative Example 7: This comparative example is a blank control group.
[0052] This comparative example discloses a flexible flame-retardant gel comprising the following raw materials in parts by weight: 179,950 parts polyvinyl alcohol, 3 parts silver nanowires, and 7 parts phytic acid.
[0053] The preparation method of the flexible flame-retardant gel includes the following steps: S1. Polyvinyl alcohol-1799 was dissolved in DMSO at 90°C with stirring to obtain solution A; silver nanowires were ultrasonically dispersed in anhydrous ethanol to obtain suspension C; phytic acid was dissolved in DMSO to obtain solution F; S2. While stirring, slowly pour solution A into suspension C, stir until homogeneous, then add solution F and continue stirring until homogeneous to obtain the fourth mixture; S3. Add the pentanediol aqueous solution to the fourth mixture, add HCl dropwise to adjust the pH to 2-3, let the reaction stand for 1-4 hours to obtain the fifth mixture; S4. Immerse the fifth mixture in ethanol, allow it to age by displacement, remove the solid, and dry it with supercritical CO2 to obtain an aerogel.
[0054] The concentration of ethanol in S4 is 25%, 50%, 75%, and 100%, and each soaking lasts for 8 hours.
[0055] Experimental verification: 1. Testing of material compressive strength and peel strength.
[0056] The aerogels prepared in the examples and comparative examples were processed into cylindrical samples with a diameter of 15 mm and a height of 20 mm, and their compressive strength was tested using a universal testing machine.
[0057] The aerogels prepared in the examples and comparative examples were processed into sheet samples with a thickness of 1 mm. Aluminum sheets with maleimide groups on their surface were prepared, pre-cleaned and silanized, and heated and pressurized with the sheet samples at 80°C and 0.5 MPa for 30 minutes to obtain 25 mm × 25 mm bonded samples. The peel force was tested using a universal testing machine and the peel strength was calculated.
[0058]
[0059] Table 1 shows the compressive strength and peel strength of the samples in each test group. Comparing Example 1 with Comparative Examples 1, 4, and 5-7, Example 1 has a higher compressive strength, indicating that the hydrophobic treatment of graphene and the grafting of mPEG onto polyvinyl alcohol improve the dispersibility of graphene in polyvinyl alcohol, reduce agglomeration, and enhance the compressive strength of the material. Furthermore, the addition of modified graphene and epoxy resin E-51 can significantly enhance the compressive strength of the material. Comparing Example 1 with Comparative Examples 2-3, Example 1 has a higher peel strength, indicating that the modified graphene is not grafted with furan groups, and the aerogel and aluminum sheet rely only on physical adsorption, resulting in weak adhesion and lower peel strength. Additionally, when the modified polyvinyl alcohol is not grafted with DBU-(CH2)3-NCO, the furan groups are not protected, and the DA reaction sites are occupied, leading to weak subsequent adhesion and lower peel strength.
[0060] 2. Actual performance of materials in use.
[0061] The aerogels prepared in each embodiment and comparative example were processed into sheets with a thickness of 0.5 mm and firmly attached to the back of a simulated OLED screen with maleimide groups modified on the surface through a DA reaction to obtain samples.
[0062] (1). Flame retardancy test: Flame retardancy is tested according to UL 94.
[0063] (2). Conductivity test: The conductivity inside the aerogel surface was measured using the four-probe method.
[0064] (3) Thermal insulation performance: According to the JESD51 series standards, the surface temperature of the heating element and the corresponding point temperature on the OLED screen side are tested, and the temperature difference between the two is calculated and recorded as ΔT. The larger the temperature difference, the better the thermal insulation performance.
[0065] (4) Electromagnetic shielding effectiveness: Electromagnetic shielding effectiveness was tested according to ASTM D4935.
[0066] (5) Mechanical reliability: The sample is mounted on a folding tester to simulate the movement of a mobile phone hinge. After 200,000 cycles, the sample is tested for cracks and delamination.
[0067]
[0068] Table 2 shows the actual performance of the materials in each test group. Comparative Examples 5 and 7, without modified graphene, exhibited poor flame retardant properties, indicating that modified graphene promotes the formation of a dense carbon layer during combustion, effectively improving the flame retardant performance of the materials. Compared with Comparative Examples 1 and 4, Example 1 showed higher electrical conductivity, indicating that the hydrophobic treatment of the modified graphene and the modified polyvinyl alcohol grafted mPEG improved the dispersibility of the modified graphene, thereby enhancing the quality of the conductive network. Table 2 shows that Examples 1-5 exhibited a large temperature difference and good thermal insulation performance, effectively delaying screen aging. The electromagnetic shielding effectiveness of Examples 1-5 was far greater than 30dB, effectively eliminating interference from the motherboard to the screen. Furthermore, after simulating mobile phone hinge movement, no visible cracks or delamination were observed between the aerogel and the OLED screen back panel, demonstrating its good flexibility and interfacial bonding strength. Therefore, the aerogel prepared by this invention can achieve adhesive-free bonding with the back panel of OLED screens through direct chemical bonding, and has excellent flame retardancy, electrical conductivity, heat insulation, electromagnetic shielding effectiveness, and mechanical properties.
[0069] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A flexible flame-retardant gel, characterized in that, The raw materials include the following parts by weight: 5-10 parts modified graphene, 50-80 parts modified polyvinyl alcohol, 3-5 parts silver nanowires, 7-10 parts phytic acid, and 5-7 parts epoxy resin E-51. Modified graphene was hydrophobically treated and grafted with furan groups; Modified polyvinyl alcohol grafted with sterically hindered amine groups and PEG long chains.
2. The flexible flame-retardant gel according to claim 1, characterized in that, The method for preparing the modified graphene includes the following steps: S11. Mix concentrated H2SO4 and H3PO4 in an ice bath and stir continuously. Add graphite powder and disperse evenly. Slowly add KMnO4 in batches. Remove the ice bath, heat and stir the reaction. Cool the resulting reaction solution in an ice bath, add deionized water, add H2O2 solution dropwise, centrifuge to collect the solid, wash with dilute hydrochloric acid and deionized water, dialysis to purify, and freeze-dry to obtain graphene oxide. S12. Disperse graphene oxide in deionized water, ultrasonically disperse, and adjust the pH to weakly alkaline to obtain a graphene oxide dispersion. S13. Add silane coupling agent KH570 to the graphene oxide dispersion, stir and react, centrifuge the resulting reaction solution to collect the solid, wash with deionized water, freeze dry to obtain hydrophobic graphene oxide; S14. Disperse hydrophobic graphene in DMF, add furanol methanol and p-toluenesulfonic acid, reflux the reaction, centrifuge the resulting reaction solution to collect the solid, wash with ethanol and deionized water, and vacuum dry to obtain modified graphene.
3. The flexible flame-retardant gel according to claim 2, characterized in that, The mass ratio of graphene oxide, furanol, and KH570 is 1:8~9:7~8, and the mass of p-toluenesulfonic acid is 3% of the mass of furanol.
4. The flexible flame-retardant gel according to claim 1, characterized in that, The method for preparing the modified polyvinyl alcohol includes the following steps: S21. Dissolve polyvinyl alcohol in anhydrous DMSO, cool the resulting solution, add DBTL, and then slowly add a DMSO solution of DBU-(CH2)3-NCO. Stir the reaction to obtain the first compound. S22. Cool the first compound, pour it into ice-cold acetone to precipitate, collect the solid by centrifugation, wash it repeatedly with acetone and centrifuge, and dry it under vacuum to obtain the second compound. S23. Dissolve mPEG and HDI in anhydrous DMF, add DBTL, activate the reaction, and obtain the third compound; S24. The second compound was heated and dissolved in anhydrous DMF, the third compound was slowly added dropwise, followed by DBTL, and the reaction was heated. The resulting reaction solution was cooled and poured into ice-cold ether to precipitate. The solid was collected by centrifugation, washed repeatedly with ether by centrifugation, and dried under vacuum to obtain modified polyvinyl alcohol.
5. The flexible flame-retardant gel according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol, DBU-(CH2)3-NCO, and mPEG is 5:1.5~2:24~27, and the molar ratio of mPEG to HDI is 3:
1.
6. A method for preparing a flexible flame-retardant gel, applied to the preparation of a flexible flame-retardant gel as described in any one of claims 1 to 5, characterized in that, The method includes the following steps: S1. Dissolve modified polyvinyl alcohol in DMSO with stirring to obtain solution A; disperse modified graphene in deionized water with ultrasonication to obtain suspension B; disperse silver nanowires in anhydrous ethanol with ultrasonication to obtain suspension C; dissolve epoxy resin E-51 and phytic acid in DMSO to obtain solution D. S2. While stirring, slowly pour solution A into suspension B, sonicate to disperse evenly, slowly add suspension C and stir evenly, continue to add solution D, continue to stir and mix evenly to obtain the first mixture; S3. Add pentanediol aqueous solution to the first mixture, add HCl dropwise to adjust the pH, let the reaction stand, and obtain the second mixture; S4. Dissolve methyltetrahydrophthalic anhydride and zinc acetylacetonate in DMSO to obtain solution E, slowly diffuse it into the second mixture, heat and solidify to obtain the third mixture; S5. Immerse the third mixture in ethanol, allow it to age by displacement, remove the solid, and dry it with supercritical CO2 to obtain an aerogel.
7. The method for preparing a flexible flame-retardant gel according to claim 6, characterized in that, The concentration of ethanol in S5 is 25%, 50%, 75%, and 100%, and each soaking lasts for 8 hours.
Citation Information
Cited By
Preparation method of isotropic graphite material paste for thorium-based molten salt reactor
CN121107853A
A method for preparing isotropic graphite material paste for thorium-based molten salt reactor
CN121107853B